Nothing lasts forever ebook - Grace, Sina (Image Comics, 2018)
Cartoonist SINA GRACE returns with another chapter in his growing library of reflective memoirs, producing his strongest and most compelling tale to date. Chronicling a year of heartbreaks, writerês block, career highs, emotional lows, and the emergence of a mystery illness, NOTHING LASTS FOREVER is Graceês unflinching exploration of how to pick up the pieces and find hope when absolutely everything falls apart. If lifeês a show, GRACE makes certain that itês worth every pay-per-view. Author: Sina Grace. Illustrator: Sina Grace. 2017 Sina Grace.